Study on C6-C3 Skeleton Derivatives from the Flower Buds of Magnolia denudata - Li, Jun; Yang, Guangzhong; Mei, Zhiyi; Huang, Xianju; Zhang, Hualin (Asian Journal of Chemistry, 2015)
The chemical constituents of flower buds of Magnolia denudata Desr. were investigated. We isolated and identified five furofurans type lignan (1, 2, 3, 4, 5), three Phenylpropanoid type derivatives (6, 7, 8), one dihydrofuran type lignan (9), one flavonoid glycoside (10) and dibutyl phthalate (11) from M. denudate. The structures of these compounds were elucidated based on the chemical and 1H NMR, 13C NMR and MS spectroscopic evidence.